Al-Maraghi’s Interpretation of QS. al-Kahf: 23–24 and Its Relevance to Perfectionism - Sinata, Dewi; Ahmad Saerozi (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2025)
Abstract Perfectionism is a psychological condition in which a person tends to set very high standards and show excessive control, so it requires a value-based approach that can create a better balance. This article discusses the correlation between al-Maraghi’s interpretation of QS. al-Kahf: 23–24 and perfectionistic attitudes. The study uses qualitative library research, an Islamic psychology approach, and content analysis. The findings reveal that these verses embody three central values: trusting Allah without excessive control, remembering Allah in every plan, and being mindful of human limitations. These values are relevant for managing perfectionist tendencies and preventing their negative impact on mental health. The results also suggest that al-Maraghi’s tafsir offers a Qur’anic perspective that can be applied to address modern psychological challenges, making an interdisciplinary contribution to tafsir studies and personality psychology. Further research is recommended to explore other verses or the works of other mufassir to enrich the discussion. Keywords: Al-Maraghi’s Tafsir; Islamic Psychology; Perfectionism; Surah al-Kahf: 23–24.